Screening for Distress in Oncological Patients: The Revised Version of the Psychological Distress Inventory (PDI-R) - Rossi, Alessandro Alberto; Marconi, Maria; Taccini, Federica; Verusio, Claudio; Mannarini, Stefania (Frontiers in Psychology, 2022)
Background. Psychological research in oncological settings is steadily increasing and the construct of psychological distress has rapidly gained popularity – leading to the development of questionnaires aimed at its measurement. The Psychological Distress Inventory (PDI) is one of the most used instruments, but its psychometric properties were not yet deeply evaluated. The present studies aimed at investigating the psychometric properties of the PDI (Study1) and providing a revised version of the tool (Study2). Methods. Oncological outpatients were enrolled at the Department of Medical Oncology of the Presidio Ospedaliero of Saronno, ASST Valle Olona, Italy. For the first study (N = 251), an Exploratory Graph Analysis was used to explore the item structure of the PDI. In the second study (N = 902), the psychometric properties of the revised PDI (PDI-R) were deeply assessed. Results. Study1 showed that the PDI has a not clear structure and it should be reconsidered. On the opposite, Study2 showed that the revised version (PDI-R) has a solid factorial structure, it is invariant across gender and age, and it has good psychometric properties. Conclusion: Results suggest that the PDI-R is a reliable measure of psychological distress in different samples of oncological patients, with stronger psychometric properties than the original version. Its use in the clinical and research field is therefore recommended to improve the quality of both assessment and treatment ofpsychological distress in patients with oncological problems.